(NwYS[AQ MATEMATIKA (B:s [(Nu^EBNOE POSOBIE(B] /s - (NkREPAK(B, (NwALERIJ nIKOLAEWI^s; (NmELENTXEW(B, (NbORIS wASILXEWI^s; (NrOMANOW(B, (NpETR pAWLOWI^s ((NmOSKWA (B:s (NwSESO@ZNOGO ZAO^NOGO POLITEHNI^ESKOGO IN(B-(NTA(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 316 (7 (NNAZW(B.)s
(NnA OBL(B. (NAWT(B. (NNE UKAZANYs
Keywords: (NmATEMATIKA WYS[AQs